Tight finite-key analysis for quantum key distribution without monitoring signal disturbance - Hang Liu (Nature Portfolio, 2021)
Abstract Unlike traditional communication, quantum key distribution (QKD) can reach unconditional security and thus attracts intensive studies. Among all existing QKD protocols, round-robin-differential-phase-shift (RRDPS) protocol can be running without monitoring signal disturbance, which significantly simplifies its flow and improves its tolerance of error rate. Although several security proofs of RRDPS have been given, a tight finite-key analysis with a practical phase-randomized source is still missing. In this paper, we propose an improved security proof of RRDPS against the most general coherent attack based on the entropic uncertainty relation. What’s more, with the help of Azuma’s inequality, our proof can tackle finite-key effects primely. The proposed finite-key analysis keeps the advantages of phase randomization source and indicates experimentally acceptable numbers of pulses are sufficient to approach the asymptotical bound closely. The results shed light on practical QKD without monitoring signal disturbance.